Repurposing of Doxycycline to Hinder the Viral Replication of SARS-CoV-2: From in silico to in vitro Validation - Alexpandi, Rajaiah; Gendrot, Mathieu; Abirami, Gurusamy; Delandre, Océane; Fonta, Isabelle; Mosnier, Joel; Mariadasse, Richard; Jeyakanthan, Jeyaraman; Pandian, Shunmugiah Karutha; Pradines, Bruno; Ravi, Arumugam Veera (Frontiers in Microbiology, 2022)
Since the rapid spread of coronavirus disease (COVID-19) became a global pandemic, healthcare ministries around the world have recommended certain control methods such as quarantining infected persons, identifying infections, mask wearing and hand hygiene. Since no effective treatment for COVID-19 has yet been discovered, a variety of drugs approved by Food and Drug Administration (FDA) have been suggested for repurposing strategy. In the present study, we predicted that doxycycline could interact with the nucleotide triphosphate (NTP) entry channel, and is therefore expected to hinder the viral replication of SARS-CoV-2 RNA-dependent RNA-polymerase (RdRp) through docking analysis. Further, the molecular dynamics results revealed that the RdRp-Doxycycline complex was structurally relatively stable during the dynamic period (100 ns), and its complex maintained close contact with their active catalytic domains of SARS-CoV-2 RdRp. The molecular mechanics Poisson–Boltzmann surface area (MM-PBSA) calculation of binding free energy also showed that the doxycycline has worthy affinities with SARS-CoV-2 RdRp. As expected, doxycycline effectively inhibited the viral replication of SARS-CoV-2 IHU strains (IHUMI-3 and IHUMI-6), identified from the hospitalized patients in IHU Méditerranée Infection (IHUMI), Marseille, France. Moreover, doxycycline inhibited the viral load in vitro at both on-entry and after viral entry of IHU variants of SARS-CoV-2. The results suggest that doxycycline exhibits variant-dependant antiviral activity. Hence, the present study concludes that doxycycline could be more helpful in combination with other drugs for better treatment efficacy against COVID-19.